Bonding of universal adhesives to dentine – Old wine in new bottles?. Issue 5 (May 2015) - Chen, C.; Niu, L.-N.; Xie, H.; Zhang, Z.-Y.; Zhou, L.-Q.; Jiao, K.; Chen, J.-H.; Pashley, D.H.; Tay, F.R.
Abstract: Objective: Multi-mode universal adhesives offer clinicians the choice of using the etch-and-rinse technique, selective enamel etch technique or self-etch technique to bond to tooth substrates. The present study examined the short-term in vitro performance of five universal adhesives bonded to human coronal dentine. Methods: Two hundred non-carious human third molars were assigned to five groups based on the type of the universal adhesives (Prime&Bond Elect, Scotchbond Universal, All-Bond Universal, Clearfil Universal Bond and Futurabond U). Two bonding modes (etch-and-rinse and self-etch) were employed for each adhesive group. Bonded specimens were stored in deionized water for 24 h or underwent a 10, 000-cycle thermocycling ageing process prior to testing ( N  = 10). Microtensile bond testing (μTBS), transmission electron microscopy (TEM) of resin–dentine interfaces in non-thermocycled specimens and scanning electron microscopy (SEM) of tracer-infused water-rich zones within hybrid layers of thermocycled specimens were performed. Results: Both adhesive type and testing condition (with/without thermocycling) have significant influences on μTBS. The use of each adhesive in either the etch-and-rinse or self-etch application mode did not result in significantly different μTBS to dentine. Hybrid layers created by these adhesives in the etch-and-rinse bonding mode and self-etch bonding mode were ∼5 μm and ≤0.5 μm thick respectively. Tracer-infused regions could be identified within the resin–dentine interface from all the specimens prepared. Conclusion: The increase in versatility of universal adhesives is not accompanied by technological advances for overcoming the challenges associated with previous generations of adhesives. Therapeutic adhesives with bio-protective and bio-promoting effects are still lacking in commercialized adhesives. Clinical significance: Universal adhesives represent manufacturers' attempt to introduce versatility in product design via adaptation of a single-bottle self-etch adhesive for other application modes without compromising its bonding effectiveness.